Contemporary Management Accounting Techniques and Organizational Performance - Dahal, Rewan Kumar (Pravaha, 2020)
The study's purpose was to observe the degree of association of contemporary management accounting techniques (CMATs) with organizational performance (OP). A survey questionnaire instrument was employed to collect data and followed a descriptive research design. The populace comprised all the manufacturing companies that were functioning in Nepal and their employees. The study targeted the listed manufacturing companies in Nepal Stock Exchange and their employees as a sample. A sum of 570 respondents had partaken in the survey using a random sampling technique, and 387 responses were filled correctly up for further analysis. The survey questionnaire had two questions relating to the respondents' general information, 12 questions regarding CMATs, and five questions relating to the effect of the study variables on OP. The study uncovered a negative and significant association between the variables that indicated the Nepalese manufacturing companies (NMCs) need to focus on fitting CMATs into organizational context. Researchers and professionals may utilize this study's outcome to upturn their insights, which thusly encourages them to assist the NMCs in improving organizational efficacy.